2016
DOI: 10.1097/aln.0000000000001342
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Wakefulness, Sleep, and General Anesthesia

Abstract: Background Significant advances have been made in our understanding of subcortical processes related to anesthetic- and sleep-induced unconsciousness, but the associated changes in cortical connectivity and cortical neurochemistry have yet to be fully clarified. Methods Male Sprague–Dawley rats were instrumented for simultaneous measurement of cortical acetylcholine and electroencephalographic indices of corticocortical conne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
111
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(128 citation statements)
references
References 68 publications
13
111
1
Order By: Relevance
“…These EEG dynamics similarities between them are in line with the findings that GABAergic neural circuit mechanisms behave [3,26,31]. This implies that highly structured thalamocortical oscillations that communicate with cortical information processing, as well as slow oscillations in cortical activity [9,32], which are responsible for this phenomenon.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…These EEG dynamics similarities between them are in line with the findings that GABAergic neural circuit mechanisms behave [3,26,31]. This implies that highly structured thalamocortical oscillations that communicate with cortical information processing, as well as slow oscillations in cortical activity [9,32], which are responsible for this phenomenon.…”
Section: Discussionsupporting
confidence: 71%
“…This kind of anesthetic-induced and reversible unconsciousness state is known to be manipulated by anesthesiologists, bringing many benefits to humans, undoubtedly. Surprisingly, even with increasingly rich knowledge about anesthetic molecular pharmacology and clinical behavior, the underlying neural interaction circuit mechanisms for patient's consciousness is still far from being fully understood [3]. In practice, experienced anesthesiologists an induction agent for the sedation and maintenance one of general anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of norepinephrine blockade on the POA, in particular, has wide ranging ‘upstream’ effects involving several neurotransmitters and neural networks, leading to decreased arousal, sleep-like states or deep sedation 18 . In contrast, isoflurane (a halogenated inhalational anesthetic) exerts its effects by acting on a wide variety of voltage- and ligand-gated channels including GABA A , glycine, nicotinic acetylcholine receptors, NMDA and K channels 19,38 , which are located throughout the brain and spinal cord. The effects of isoflurane on LC neurons and NE are not as clear cut as those of dexmedetomidine.…”
Section: Discussionmentioning
confidence: 99%
“…Although a subset of studies show differing results (Barrett et al, 2012; Nicolaou et al, 2012; Maksimow et al, 2014), the disrupted frontal-parietal connectivity has also been demonstrated using functional magnetic resonance imaging (fMRI; Hudetz and Mashour, 2016). In addition, general anesthetic suppression of FB has also been reported in rodents (Imas et al, 2006; Pal et al, 2016), ferrets (Wollstadt et al, 2017), and monkeys (Lamme et al, 1998; Papadopoulou et al, 2015). Note, however, that Wollstadt et al (2017) show that FB (prefrontal cortex to V1) is reduced, but that this reduction may be a result of reduced “source information” within the prefrontal cortex.…”
Section: Introductionmentioning
confidence: 90%